2023
DOI: 10.3390/plants12061299
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Hg-, Cr-, Cu-, and Zn-Induced Heavy Metals Stress by Exogenous Sodium Nitroprusside in Rice Plants

Abstract: The cultivation of rice is widespread worldwide, but its growth and productivity are hampered by heavy metals stress. However, sodium nitroprusside (SNP), a nitric oxide donor, has been found to be effective for imparting heavy metals stress tolerance to plants. Therefore, the current study evaluated the role of exogenously applied SNP in improving plant growth and development under Hg, Cr, Cu, and Zn stress. For this purpose, heavy metals stress was induced via the application of 1 mM mercury (Hg), chromium (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…Appropriate levels of Cr can enhance net photosynthesis and promote healthy plant growth, but excessive Cr can have toxic effects on plants (Taufikurahman et al, 2019). Cu can be absorbed and utilized by plants to synthesize various enzymes and participate in numerous essential metabolic reactions within the plant's body (Niyoifasha et al, 2023). The biosynthesis of several enzymes in plants necessitates the utilization of zinc, and these enzymes hold particular importance for the metabolism of carbon and nitrogen in plants (Liu et al, 2022).…”
Section: Analysis Of Heavy Metal Content In Plantsmentioning
confidence: 99%
“…Appropriate levels of Cr can enhance net photosynthesis and promote healthy plant growth, but excessive Cr can have toxic effects on plants (Taufikurahman et al, 2019). Cu can be absorbed and utilized by plants to synthesize various enzymes and participate in numerous essential metabolic reactions within the plant's body (Niyoifasha et al, 2023). The biosynthesis of several enzymes in plants necessitates the utilization of zinc, and these enzymes hold particular importance for the metabolism of carbon and nitrogen in plants (Liu et al, 2022).…”
Section: Analysis Of Heavy Metal Content In Plantsmentioning
confidence: 99%
“…In addition to its role in abiotic stress tolerance, MEL has been found to act as a protectant against heavy metal (HM) stress in plants. HMs, such as lead, mercury, cadmium, and arsenic, accumulate in the soil and pose a significant threat to plant growth and development [ 103 , 104 ]. However, MEL protects plants from the toxic effects of HMs through chelation [ 105 ].…”
Section: Role Of Mel In the Mitigation Of Abiotic Stressesmentioning
confidence: 99%
“…Furthermore, studies have demonstrated the beneficial impact of hydroxyapatite nanoparticles on maize plant growth under salt-stress conditions [27]. In another study, the application of silver nanoparticles (AgNPs) resulted in an upregulation of genes related to the IAA, NCED3 (9-cis carotenoid dioxygenase), and RD22 proteins in Arabidopsis thaliana under abiotic stress [28].…”
Section: Introductionmentioning
confidence: 99%